Relationships Between Plasminogen-Binding M-Protein and Surface Enolase for Human Plasminogen Acquisition and Activation in Streptococcus pyogenes - Ayinuola, Yetunde A.; Tjia-Fleck, Sheiny; Readnour, Bradley M.; Liang, Zhong; Ayinuola, Olawole; Paul, Lake N.; Lee, Shaun W.; Fischetti, Vincent A.; Ploplis, Victoria A.; Castellino, Francis J. (Frontiers in Microbiology, 2022)
The proteolytic activity of human plasmin (hPm) is utilized by various cells to provide a surface protease that increases the potential of cells to migrate and disseminate. Skin-trophic Pattern D strains of Streptococcus pyogenes (GAS), e.g., GAS isolate AP53, contain a surface M-protein (PAM) that directly and strongly interacts (Kd ~1 nM) with human host plasminogen (hPg), after which it is activated to hPm by a specific coinherited bacterial activator, streptokinase (SK2b), or by host activators. Another ubiquitous class of hPg binding proteins on GAS cells include “moonlighting” proteins, such as the glycolytic enzyme, enolase (Sen). However, the importance of Sen in hPg acquisition, especially when PAM is present, has not been fully developed. Sen forms a complex with hPg on different surfaces, but not in solution. Isogenic AP53 cells with a targeted deletion of PAM do not bind hPg, but the surface expression of Sen is also greatly diminished upon deletion of the PAM gene, thus confounding this approach for defining the role of Sen. However, cells with point deletions in PAM that negate hPg binding, but fully express PAM and Sen, show that hPg binds weakly to Sen on GAS cells. Despite this, Sen does not stimulate hPg activation by SK2b, but does stimulate tissue-type plasminogen activator-catalyzed activation of hPg. These data demonstrate that PAM plays the dominant role as a functional hPg receptor in GAS cells that also contain surface enolase.